The Axial Compression Capacity of Finger-Jointed Laminated Board Made from Rubber Wood Species - Awaludin, Ali; Sulhan, Muhammad Afif; Effendi, Mahmud Kori; Hassan, Rohana (Civil Engineering Dimension, 2025)
The utilisation of Rubberwood was an effort to provide an alternative to low-cost housing in Indonesia. This study investigated the use of Rubberwood Finger-Jointed Laminated Board (FJLB) under compression loading parallel to the grain. The investigation included laboratory experiments and numerical analysis. The experiments were conducted using two specimens of FJLB members, each with a length of 2000 mm and a cross-sectional dimension of 100 mm × 100 mm². Finite element analysis (FEA) was employed to predict the axial capacity, considering non-linearity, contact boundary conditions, and buckling analysis of the material. The study found an average axial capacity of 150.9 kN for the two specimens, which was 3.2% higher than the FEA and 5.4% higher compared to the Euler formula. Laboratory measurements revealed that initially, the stress distribution in the cross-section was uniform, then suddenly changed to a combination of tension and compression during the final loading stage.